DSC study of mixtures of wheat flour and potato, sweet potato, cassava, and yam starches - Sarker, Md. Zaidul Islam; Absar, Nurul; Kim, Sun-Ju; Suzuki, Tatsuro; Abdul Karim, Aidah; Yamauchi, Hiroaki; Noda, Takahiro (Elsevier Inc., 2008)
Differential scanning calorimetry (DSC) traces at a 30 wt% suspension were studied for mixture of wheat flour and following starches: potato (PS), sweet potato (SPS), yam (YS), and cassava (CS) at 10% to 50% starch. In the endothermal transition, the gelatinization peak temperature of the first peak (TP1) was attributed to the wheat flour and that of the second peak (TP2), to the starches. The TP1 of the control wheat flour was lower (62.6 C) than the TP2 of the control PS (67.1 C), SPS (77.6 C), YS (67.2 C), and CS (69.7 C). In the endotherm of the mixtures, the TP1 was always closer to that of control wheat (about 62 C). In contrast, the TP2 of the mixtures was always shifted towards higher values than those of the control starches. However, the TP2 was found to be lower as the starch in the mixtures was increased, and the values ranged from 68.6 to 69.4 C, 80.1 to 82.2 C, 69.3 to 70.7 C, and 73.3 to 74.3 C for the wheat–PS, wheat–SPS, wheat–YS, and wheat–CS mixtures, respectively, at 10% to 50% starch. The apparent shifting towards higher temperatures resulted in a more prominent biphasic gelatinization behavior due to the influence of the wheat gluten in the mixtures of wheat flour and starches.